The PENGARUH DEBT TO EQUITY RATIO TERHADAP PERATAAN LABA - Suratminingsih (Jurnal Manajemen Bisnis dan Keuangan, 2020)
This study aims to examine the effect of debt to equity ratio (DER) on income smoothing in manufacturing companies listed on the BEI subsector of the consumer goods industry and various industries with a period of four years, namely the year 2016-2019 with the method of purposive judgment sampling. The statistical analysis used in this study is descriptive statistical analysis and by using logistic regression analysis through multivariate testing. Eckel index is used to classify companies that do and do not practice income smoothing. The analysis shows that debt to equity ratio (DER) with significant value 0,005 have positive effect on income smoothing